Sensitivity analysis of heat exchanger design to uncertainties of correlations. (25th May 2018) - Lambert, Julien; Gosselin, Louis
Highlights: Large errors from correlations propagate in total cost estimate of heat exchangers. Probability distributions of total cost for three test cases exhibited large variance. Total cost is highly sensitive to error on purchase cost and shell side convection. Uncertainty on cost of energy has a smaller effect on the total cost evaluation. Minimizing simultaneously expected cost and standard deviation optimal designs. Abstract: Heat exchanger design procedures rely on a series of correlations to estimate heat transfer coefficients, pressure drops, costs, etc. Each correlation is characterized by uncertainties, i.e. it returns an approximate value of the variable that it aims at predicting. This paper studies how sensitive the total cost evaluation is to these uncertainties for shell-and-tube heat exchangers. A variance decomposition approach is used to calculate the total effect of each uncertain variable. Three test cases are studied for which the most influential uncertainties were found to be those on the correlations for evaluating the purchase cost and the shell side heat transfer coefficient. Probability distributions of the total cost are presented and exhibit a large variance of the total cost. The impact of the cost of energy was also investigated, which revealed that uncertainty on energy cost had a smaller total effect than that of other variables.